ANALYSIS OF THE ISSUE OF RIGHTS IN ISLAM (American Journal of Research in Humanities and Social Sciences, 2022)
The subject is the rights of the individual in Islam, issues related to disputed rights in Islamic law, the right to life, the right to freedom, the right to equality, the right to equality in the use of resources, protection from aggression, the right to believe, think and speak, the reputation of each person, property Issues such as life protection were briefly analyzed.